Inovação em modelos de negócios sustentáveis e a contribuição do design centrado no usuário - Kurek, Juliana (2023)
The process of integrating sustainability into business models, modeling and processes is still recent, both in startups, small and medium-sized companies and even multinationals. Design thinking, for example, presents an iterative and user-centered problem-solving approach, and has recently attracted research interest as a possible approach to solving socio-environmental problems. Thus, the general objective of the thesis is to evaluate the contribution of user-centered design to enable innovation in sustainable business models. The methodological procedure used was design science research, which included a review of the state of the art on the topics of innovation in business models, sustainability-oriented business models, as well as the models and toolkits used by design, especially sustainability-oriented proposals. The proposed model focused on identifying and developing a set of tools and methods to design a sustainable business model and a value network for entrepreneurs/innovators with sustainability-oriented values, supported by design thinking, lean startup and agile methods. The proposal (of the model) aims to fill the gap identified in the systematic literature review that deals with contemplating the prototyping and testing process in sustainable business modeling. The results, from the application and validation of the model, contribute to the advancement of research in sustainable business models by discussing the use of tools and techniques for this modeling.